Forming a circle*: The practice of Forsøgsscenen (the Experimental Stage) in the self-organised political-artistic milieu of 1930s Denmark - Ullerup Schmidt, Cecilie (Peripeti, 2023)
Forsøgsscenen (The Experimental Stage, 1929-31) is examined as a historically early example of community-organising artistic practice. By analysing Forsøgsscenen based on cultural objects such as their production of a little magazine, their distribution policy and their infrastructural performance, the scholarly inquiry is shifted from the reception of the artwork in theatre history, towards approaching a materialist understanding of Forsøgsscenen's production aesthetic contribution in avant-garde history. Historiographically, a comparativist perspective is employed, which finds kinship both between collective organisations in the 1930s and kinship with contemporary concepts of self-institutionalisation as counterculture: redistributive, political and institution-forming practices that unfold as a response to the common art institutions in late capitalism.